Ethnography and Biblical Studies: ‘A Land Flowing with Milk and Honey’ as a Case Study for Re-contextualising a Familiar Phrase - Welton, Rebekah (Biblical interpretation, 2022)
The expression ‘a land flowing with milk and honey’ has traditionally been understood to refer to the abundance of food and fertility in the promised land. However, this article argues that this phrase has become overly familiar and thus certain strategies should be employed in order that contemporary, dominating assumptions about milk and honey in biblical texts may be reconsidered. In order that biblical scholars may refrain from imposing their own expectations or ideologies onto the ancient Israelites and Judahites, ethnographic data that exposes us to a diversity of alternative understandings in relation to food are worth being aware of prior to biblical exegesis. Through exposure to the use of dairy products and the connotations of honey as reported in ethnographic scholarship, this article offers a re-conceptualisation of what milk and honey may refer to as a pair in biblical texts. As a consequence, the benefits of such inter-disciplinary methods are made apparent.